Managing discomfort and developing participation in non-emergency MRI: Children's coping strategies during their first procedure. Issue 1 (February 2019) - Kada, S.; Satinovic, M.; Booth, L.; Miller, P.K.
Abstract: Introduction: Building on existing work, this paper aims to develop a detailed analysis of the practical coping strategies developed by children who had not previously experienced an MRI, regarding a non-emergency examination of the brain. Methods: Semi-structured interviews with 22 children, aged between eight and sixteen years, were conducted immediately post-procedure. Emergent data were thematically analysed in line with the core precepts of Grounded Theory, and triangulated against interview data with their parents where pertinent. Results: The primary concern among interviewees related to how they had coped with the discomfort of an unfamiliar medical procedure; this was recurrently managed through a process herein termed Participation Development . This comprised three phases. The first, preparative participation, describes the children's reported attempts to ready themselves for the examination (with parents) ahead of arriving in hospital. The second, enabling participation, describes how the children (with input from parents and radiographers) endeavoured to understand what was to come, and select viable distraction techniques. Finally, sustaining participation describes the children's reports of actualizing their preparations during the examination itself. Where the overall process of participation development was successful, the children reported a sense of mastery, growth and even joy. Conclusion: While much work in the domain portrays children as relatively 'passive' agents during an MRI procedure, the findings herein point to how they can (with varying degrees of success) actively and constructively work with others. This, it is contended, has direct import for the improvement of support, both prior to and within a procedure itself. Highlights: Children are not just 'small adults'; they have needs that require careful individual attention. Children are often rational; they value being treated as active agents in their own healthcare. Anxiety in paediatric MRI can be attenuated with careful preparation, involving relevant others. Distraction techniques in MRI require a strong read on a child's interests and values. Radiographers show strong social skills in reading paediatric patients' needs during MRI.